Нейронні мережі для аналізу мультимедійних даних - Спасибін, М. Р. (ХНУРЕ, 2020)
The article describes the approach that is used by a neural network to analyze and recognize objects in the multimedia data. Advantages and disadvantages of neural networks are defined with conditions and advise of using. Also, the article clarifies the structure of neural network, the definition of the perceptrons and the process of training them for recognizing shapes, colors and other criteria.